Microscopic study of granular material behaviours under general stress paths - Yang, Dunshun (2014)
The granular material behaviour is determined by the local contact behaviour between particles and the spatial arrangement of particles. Investigation of particle-scale mechanism provides fundamental insights into global granular material behaviour. A multi-scale investigation has been carried out to study granular material behaviour under general stress paths using discrete element method (DEM). The commercial software Particle Flow Code in Three Dimensions (PFC3D) is employed for numerical simulations and the linear contact model is used to describe local contact behaviour. General loading paths were achieved by implementing a boundary control programme with independent control of both the magnitudes of three principal stresses and their principal directions. The intermediate principal stress ratio , where are the major, intermediate and minor principal stresses, and material anisotropy both had significant effect on granular material strength. The true triaxial simulation results indicated that the peak stress ratio was mainly contributed by the micro-scale contact force anisotropy. A smaller stress ratio was observed at greater a b value due to smaller degree of contact force anisotropy. Fabric anisotropy was another contributor to the material stress state. A lower peak stress ratio was obtained at a larger tilting major principal stress direction from the vertical deposition direction since smaller fabric anisotropy degree developed at larger . However, the material initial anisotropy had negligible effect on the critical stress ratio owing to the same contact force anisotropy and fabric anisotropy achieved.